Комерціалізація інноваційної продукції машинобудівних підприємств - Косцик, Романа Степанівна (Національний університет "Львівська політехніка", 2016)
Дисертаційну роботу присвячено вирішенню наукового завдання щодо формування теоретико-методологічних та прикладних засад здійснення комерціалізації інноваційної продукції машинобудівних підприємств. Вперше запропоновано полікритеріальну модель вибору методів комерціалізації інноваційної продукції машинобудівних підприємств, яка ґрунтується на врахуванні низки визначених чинників. Розвинуто процес комерціалізації інноваційної продукції машинобудівних підприємств, удосконалено модель самостійної комерціалізації інноваційної продукції машинобудівних підприємств за методом її реалізації на ринку. Розвинуто класифікацію інноваційної продукції підприємств та удосконалено класифікацію методів комерціалізації інноваційної продукції машинобудівних підприємств за формами її здійснення. Диссертационная работа посвящена решению научной задачи по формированию теоретико-методологических и прикладных рекомендаций осуществления коммерциализации инновационной продукции машиностроительных предприятий. Впервые предложено поликритериальную модель выбора методов коммерциализации инновационной продукции машиностроительных предприятий, основанную на учете ряда определенных факторов. Развито процесс коммерциализации инновационной продукции машиностроительных предприятий, усовершенствована модель самостоятельной коммерциализации инновационной продукции машиностроительных предприятий по методу реализации на рынке. Развито классификацию инновационной продукции предприятий и усовершенствована классификация методов коммерциализации инновационной продукции машиностроительных предприятий по формам ее осуществления. The thesis is devoted to solving of scientific tasks in relation to the formation of theoretic-methodological and applied recommendations for implementation of commercializing innovative products of machine-building enterprises. For first time it was offered a poli-criterial selection model of commercializing innovative products methods of machine-building enterprises, based on the consideration of a number of specified factors. Commercialization process of innovative products by machine-building enterprises was improved, and the model of self-commercializing of innovative products for machine-building enterprises according to the method of its implementation on the market was formed. The classification of enterprises’ innovative products and classification of commercializing innovative products methods by machine-building enterprises by forms of its implementation have been improved. In the first chapter «Theoretical and applied principles of commercializing innovative products of machine-building enterprises» the essence and role of commercializing innovative products of enterprises were considered, the enterprises’ innovative products were discussed as an object of commercialization, the classification of product innovation on enterprises was specified and expanded. It was offered to consider as commercializing of innovative products the process of its marketing in order to obtain economic benefits and the stages of this process were improved. The machine-building enterprises’ innovative products are proposed to be taken as a result of the enterprise activity, which is reflected in the totality of products (goods, performance and services) produced over a certain period of time, resulting in fundamental and applied researches and developments, and which include certain intellectual property and aim at ensuring the progressive development of the enterprise. Also the chapter contains a comprehensive classification of enterprises’ innovative products, taking into account the following classification criteria: the role of use, the level of innovation, the needs fulfiling, in respect of the resulting effect, effectiveness, direction of realization, branch affiliation, level of implementation coverage, the volume of market coverage, the mass usage, purpose, direction, belonging to development, by sources of funding. In the second chapter «Analysis of commercializing innovative products of enterprises’ condition» the complex method of analyzing the condition of commercialization is formed, and also the preconditions for activating the commercializing innovative products of the enterprises are investigated and the business analysis of its status at the corresponding enterprises is performed. In this chapter was offered a model for analysis of commercializing innovative products of machine-building enterprises, which consists of the following stages: setting the goals for analyzing of commercializing innovative products of enterprises; forming the methods of analysis; forming the basis for analysis; communication with enterprises; consolidation of results; processing of results; forming conclusions. Within the stage of formation of analysis methods was proposed a complex method due to which the review of commercializing innovative products’ status of machine-building enterprises will be implemented in full. The proposed comprehensive method consists of an expert survey (questionnaire) and a quantitative analysis of the enterprise’s indexes derived from the financial, accounting and management reporting. Based on the elaborated stages of analysis of commercializing innovative products of machine-building enterprises, we conducted an evaluation of the commercialization condition of machine-building enterprises in the city of Lviv. The following problems were dentified while commercializing innovative products of machine-building enterprises: lack of the personnel’s competence performing the commercialization, limited financial resources for commercializing innovative products, lack of other enterprise’s resources, lack of competence of the outsourcing enterprise undertaking the commercialization. The main advantages of the commercializing innovative products were: increasing the enterprise’s level of profits, improving enterprise’s competitiveness, promoting the innovative products and its own brand, entering new sale markets, expanding the share of existing sale markets. In the third chapter of the thesis «Instrumental support for commercializing innovative products of machine-building enterprises» there was formed a model of choice of the preferred methods of commercializing innovative products for machine-building enterprises, analyzed the implementation of innovative products as a method of self-commercialization, and conducted the diagnostic efficiency of innovative products commercialization for machine-building enterprises. The current selection methods model of commercializing innovative products for machine-building enterprises is based on consideration of a number of specified factors: the ability of the enterprise’s complete resource supply, the expected effectiveness from the implementation of the innovative products, maintaining the control and responsibility center within the company, the availability on the market of the professional outsourcing enterprise that meets the requirements of the innovative production manufacturer, a single responsibility center, resources unification, focus on expanding the market share, the ability to provide consultancy services, maintaining their own brand. As a result of the analysis it was figured out that the use of innovative products for personal enterprises, its production and sale is the most rational method of innovation commercializing. The study presents the implementation stages of innovative products realization by machine-building enterprises taking into account the principles of commercializing innovative products. On the basis of the research it was proposed to consider the effectiveness of commercializing innovative products both as a level, and as a phenomenon. The level of efficiency of commercializing innovative products reflects the correlation of the obtained effect and commercialization costs. The systematic analysis of correspondent representational business indicators will help to make a conclusion on the effectiveness of the process of commercialization in the machine-building enterprises as a phenomenon.
Коммерциализация инновационной продукции машиностроительных предприятий
Commercializing innovative products of machine-building enterprises
Keywords: інновації; інноваційна продукція; комерціалізація; етапи комерціалізації; форми комерціалізації; методи комерціалізації; реалізація інноваційної продукції; инновации; инновационная продукция; коммерциализация; этапы коммерциализации; формы коммерциализации; методы коммерциализации; реализация инновационной продукции; innovation; innovative products; commercialization; commercialization stages; forms of commercialization; commercialization methods; implementation of innovative products